2013
DOI: 10.1371/journal.pone.0054195
|View full text |Cite
|
Sign up to set email alerts
|

A2A Adenosine Receptors Are Differentially Modulated by Pharmacological Treatments in Rheumatoid Arthritis Patients and Their Stimulation Ameliorates Adjuvant-Induced Arthritis in Rats

Abstract: A2A adenosine receptors (ARs) play a key role in the inhibition of the inflammatory process. The purpose of this study was to evaluate the modulation of A2AARs in rheumatoid arthritis (RA) patients after different pharmacological treatments and to investigate the effect of A2AAR stimulation in a rat model of arthritis. We investigated A2AAR density and functionality in RA progression by using a longitudinal study in RA patients before and after methotrexate (MTX), anti-TNFα agents or rituximab treatments. A2AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 49 publications
3
35
0
1
Order By: Relevance
“…Indeed, previous studies have shown a positive correlation between the number of Tfh cells and disease burden in patients with RA (26). Perhaps consistent with this, A2aR agonists effectively suppress animal models of inflammatory arthritis (27). The fact that the first-line anti-rheumatic drugs methotrexate and sulfasalazine act, in part, through the generation of extracellular adenosine and A2aR signaling (28, 29), lends further support to the notion that A2aR signaling can ameliorate T-dependent B cell autoreactivity.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, previous studies have shown a positive correlation between the number of Tfh cells and disease burden in patients with RA (26). Perhaps consistent with this, A2aR agonists effectively suppress animal models of inflammatory arthritis (27). The fact that the first-line anti-rheumatic drugs methotrexate and sulfasalazine act, in part, through the generation of extracellular adenosine and A2aR signaling (28, 29), lends further support to the notion that A2aR signaling can ameliorate T-dependent B cell autoreactivity.…”
Section: Discussionmentioning
confidence: 58%
“…In particular, A 2a is upregulated by agents that stimulate activation of NFκB (a central transcriptional regulator in the inflammatory process), such as TNF, IL-1 and endotoxin, 24-28 and acts, as described below, as a feedback inhibitor of inflammation. Evidence from patients with RA confirms these observations: increased expression of A 2a on peripheral white blood cells in these patients is reduced by treatment with anti-TNF agents 29,30 . In addition to regulation of A 2a expression, TNF and other proinflammatory cytokines increase the function of these receptors by preventing receptor desensitization 31 , further downregulating inflammation.…”
Section: Adenosine Receptorsmentioning
confidence: 58%
“…Therefore, the inhibition of both NF κ B activation and TNF‐ α release could prevent the proinflammatory positive feedback loop produced by TNF‐ α /NF κ B activation in psoriatic skin. In a similar manner, it has been described that CGS‐21680 reduces the progression of murine type II collagen‐induced arthritis (CIA) and ameliorates adjuvant‐induce arthritis in rats , both accepted animal models of rheumatoid arthritis, which are also characterized by increased levels of TNF‐ α and activation of the NF κ B signalling pathway.…”
Section: Discussionmentioning
confidence: 82%